Tumor suppressing effects of tristetraprolin and its small double‐stranded RNAs in bladder cancer. (1st December 2020) - Jiang, Wen; Zhu, Dandan; Wang, Chenghe; Zhu, Yu
Abstract: Bladder cancer (BCa) is a common malignant tumor of urinary system with few treatments, so more useful therapeutic targets are still needed. Antitumor effects of tristetraprolin (TTP) have been explored in many type tumors, but its roles in bladder cancer are still unknown until now. In this study, public expression profiles and tissue microarray analysis showed that TTP mRNA and protein levels decreased in BCa relative to the normal bladder tissue. To explore biological functions of TTP in BCa, 488 TTP target genes, which could be both suppressed and bound by TTP, were identified by comprehensively analyzing publicly available high‐throughput data obtained from Gene Expression Omnibus (GEO). Gene enrichment analysis showed that these genes were enriched in pathways such as cell cycle, epithelial to mesenchymal transition (EMT), and Wnt signaling. Clustering analysis and gene set variation analysis indicated that patients with high expression of TTP target genes had poorer prognosis and stronger tumor proliferation ability relative to the BCa patients with low expression of TTP target genes. In vitro experiments validated that TTP could suppress proliferation, migration, and invasiveness of BCa cells. And TTP could suppress mRNA expression of cyclin‐dependent kinase 1 (CDK1) in BCa cells by target its 3′ UTR. Then, we identified a new small double‐stranded RNA (dsRNA) named dsTTP‐973 which could increase TTP expression in BCa cells, in vivo and in vitro experiments revealed that dsTTP‐973 could suppress aggressiveness of BCa. In conclusion, TTP played a role of tumor suppressor gene in BCa like other tumors, and its dsRNA named dsTTP‐973 could induce TTP expression in BCa and suppress aggressiveness of BCa. With the help of materials science, dsTTP‐973 may become a potential treatment for BCa in the future. Abstract : TTP overexpression can inhibit the malignant biological behaviors of BCa, and can be a potential therapeutic target for BCa. dsTTP‐973 which can induce TTP expression in BCa is able to suppress BCa progression, and dsTTP‐973 may be a potential treatment for BCa in the future.